Education and ways of reducing nitrogen oxides in the boiler tg-104 with a direct-flow-vortex burners and the peripheral gas supply - M. A. Taymarov; R. V. Akhmetova; R. G. Sungatullin; E. G. Chiklyaev; D. E. Chiklyaev (Известия высших учебных заведений: Проблемы энергетики)
This article deals with the distribution of temperature and incident heat flux on the display surface boiler heating TG-104 at work at the Urengoy gas and the thermal efficiency of the burners to reduce the formation of nitrogen oxides. The temperature of the combustion products was measured using an optical method and thermocouple contact method. The incident heat fluxes measured by the radiometer the full radiation. Burned fuel - natural gas according to GOST 30319.1-96 with the lower heat of combustion 35146 kJ/m3.